2018
DOI: 10.1097/nnr.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Driving Performance, Self-Reported Driving Behaviors, and Mental Health Symptoms in Adolescent Novice Drivers

Abstract: These data highlight the association of risky driving with adolescent symptoms of inattention, hyperactivity, and conduct disorder. The early stage of independent driving is an important time for addressing the relationship between driving performance and mental health conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Positive relationships were found between driving simulator score and trait anxiety among the control group only. These findings support the literature evidence linking symptoms of anxiety and ADHD to dangerous driving (Mcdonald et al, 2018). It is interesting that these connections were not found for a group of adolescents with complex ADHD.…”
Section: Discussionsupporting
confidence: 91%
“…Positive relationships were found between driving simulator score and trait anxiety among the control group only. These findings support the literature evidence linking symptoms of anxiety and ADHD to dangerous driving (Mcdonald et al, 2018). It is interesting that these connections were not found for a group of adolescents with complex ADHD.…”
Section: Discussionsupporting
confidence: 91%
“…This yielded mixed results: RTB was sometimes associated with inattention, sometimes with hyperactivity/impulsivity, and sometimes with both (e.g. [14,35],). For example, De Alwis et al [36] found that the associations between substance use and either inattentive or hyperactive/impulsive symptoms were similar, except for alcohol and nicotine use that were more strongly associated with hyperactive/impulsive symptoms.…”
Section: Adhd Presentationmentioning
confidence: 99%
“…Additional exclusion criteria included current depressive episodes or current post-traumatic stress disorder (PTSD), since these conditions could potentially hamper the ability to complete the lengthy questionnaire. We controlled for other psychiatric disorders, given the high prevalence of comorbidities among our participants and their associations with abnormal levels of risk-taking behavior (Brevers et al, 2013;Brogan et al, 2010;Giorgetta et al, 2012;McDonald et al, 2018;Ramrakha et al, 2000;Sip et al, 2018;Smoski et al, 2008;Strom et al, 2012). In order to control for the presence of psychiatric disorders, all participants underwent the Hebrew version of the Structured Clinical Interview for DSM-IV Disorders (SCID; First et al, 1996).…”
Section: Participantsmentioning
confidence: 99%